The Pricing Behaviour of UK Firms - Nicoletta Batini; Brian Jackson; Stephen Nickell (Bank of England, External Monetary Policy Committee Unit, 2002)
Industrial prices of goods and services are a function of costs of production and of the mark-up that firms apply on those costs. If these prices relate to goods that are traded internationally, they will also be influenced by the price at which those goods are exchanged in international markets. In this paper we present two models of industry pricing behaviour and confront them with UK sectoral data, by estimating the theoretically derived pricing equations using an input-output table at basic prices prepared by Cambridge Econometrics and employment and wage data from the New Earnings Survey. The model based on Bils (1987) and Hall (1988) and which was originally devised for industries within the US manufacturing sector appears to fit the data only marginally better than the one which is based on a structural dynamic pricing equation from Batini, Jackson and Nickell (2000). In both models, sectoral domestic prices depend on marginal costs and sectoral world prices in domestic currency. We find that, in this respect, the weight attached to world prices is significantly correlated with the degree of openness of the industry.
Keywords: 330